Iran: being a nuclear threshold state within a national resistance context - ALAGÖZ, BİLGEHAN (My University, 2022)
For almost four decades, Iran's foreign policy rhetoric and actions have drawn the attention of the international community. Iran acquired a leadership role in the advocacy of oppressed people against oppressors after the 1979 Revolution. In this direction, it has exhibited two-pronged foreign policy behaviour over the years. One is the axis of resistance politics, and the second is the advancement of a nuclear program. The Iranian-led coalition network known as the ‘Axis of Resistance’ includes Shiite paramilitary groups in Iraq, the Syrian Ba'ath regime, Palestinian resistance organizations, and Hezbollah in Lebanon. Since the USA adopted the 'Axis of Evil’ rhetoric against Iran in 2002, Iran has simultaneously deepened its relations with the axis of resistance in the face of this pressure and has advanced its nuclear activities, which has transformed it into a nuclear threshold state. In this article, we argue that these two main foreign policy activities are inseparable and they are ultimately the consequence of Iran's adopted national role, i.e., the leader of the oppressed. Therefore, we discuss that with its resistance to the pressures relevant to the nuclear program, Iran intends to give a clear message to the proxies on the axis of resistance. We applied role theory on the relationship between the axis of resistance concept and nuclear policy to contribute to the prominent foreign policy debates over Iran's two inseparable foreign policy behaviours.

İran İslam Cumhuriyeti’nin dış politika söylem ve eylemleri kırk yılı aşkın bir süredir uluslararası toplumun odak noktasıdır. İran, 1979 İslam Devrimi sonrasında yeni bir rol üstlenmiştir; bu da ezenlerin karşısında ezilenlerin savunuculuğunu yapmaktır. Bu doğrultuda, İran yıllar içinde dış politikasında iki davranışı ön plana çıkarmıştır. Bunlardan biri, direniş ekseni siyaseti, ikincisi ise nükleer programın geliştirilmesidir. Direniş ekseni, Filistin direniş örgütleri, Lübnan Hizbullahı, Suriye'deki Esad rejimi ve Irak'taki Şii paramiliter grupları içeren İran liderliğindeki ittifak ağı için kullanılan ifadedir. ABD'nin 2002 yılında İran'a karşı 'şer ekseni' söylemini benimsemesinden bu yana, İran bu baskı karşısında eş zamanlı olarak direniş ekseni olarak tanımladığı vekillerle ilişkilerini derinleştirmiş ve eş zamanlı olarak nükleer faaliyetlerini ilerletmiş, bu da onu nükleer eşik devleti yapmıştır. Bu makalede, İran ’ ın devrimden bu yana öne çıkardığı iki ana dış politika davranışının birbirinden ayrılmaz olduğu ve bunun temel sebebinin de İran'ın benimsediği ulusal rolün, yani mazlumların liderliği rolü olduğu iddia edilmektedir. Dolayısıyla bu çalışmada, İran'ın nükleer programıyla ilgili baskılara direnmek suretiyle direniş eksenindeki vekillerine net bir mesaj vermek amacında olduğunu tartışılmaktadır. Bu bağlamda İran'ın direniş ekseni siyaseti ve nükleer politikası arasındaki ilişki, rol teorisi üzerinden ele alınmıştır.